2016
DOI: 10.3892/ol.2016.5532
|View full text |Cite
|
Sign up to set email alerts
|

AMPD3 is associated with the malignant characteristics of gastrointestinal stromal tumors

Abstract: Abstract. Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors of the gastrointestinal tract. It is well known that activating mutations in the receptor tyrosine kinases KIT and platelet-derived growth factor receptor-α have essential roles in the pathogenesis of GISTs. The activation of these receptor protein kinases triggers multiple signaling pathways that promote cell proliferation and survival; however, the exact mechanism by which the activation of these kinases promotes the progression of GIST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In our research, the elevated Slc22a5 in the hippocampus of GF mice suggests that carnitine transport and/or energy production may be increased, and thus may play a protective role. Furthermore, adenosine monophosphate deaminase 3 (Ampd3) is a key enzyme in the catabolic pathway of adenylate that breaks adenosine monophosphate into inosine monophosphate, and eventually produces uric acid 49 , 50 . Ampd3 is ubiquitously expressed; it can regulate the energy metabolism of the body and may regulate the energy balance 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research, the elevated Slc22a5 in the hippocampus of GF mice suggests that carnitine transport and/or energy production may be increased, and thus may play a protective role. Furthermore, adenosine monophosphate deaminase 3 (Ampd3) is a key enzyme in the catabolic pathway of adenylate that breaks adenosine monophosphate into inosine monophosphate, and eventually produces uric acid 49 , 50 . Ampd3 is ubiquitously expressed; it can regulate the energy metabolism of the body and may regulate the energy balance 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adenosine monophosphate deaminase 3 (Ampd3) is a key enzyme in the catabolic pathway of adenylate that breaks adenosine monophosphate into inosine monophosphate, and eventually produces uric acid 49 , 50 . Ampd3 is ubiquitously expressed; it can regulate the energy metabolism of the body and may regulate the energy balance 50 . ATP mediates lipid and protein synthesis, buffers intracellular calcium, and regulates apoptosis and resilience pathways 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Tfpi2 (tissue factor pathway inhibitor 2) inhibits the activity of matrix metalloproteinases and regulates placental perfusion [ 40 , 41 ], while deficiency of Aqp1 (aquaporin 1) causes aberrant placental vascularization and fetal overgrowth [ 37 ]. Although the consequences of altered expression of Ampd3 (AMP deaminase 3), a known regulator of fetal muscle and liver development [ 42 ], in the placenta remain to be examined, Ampd3 deficiency in cancer cells has been shown to inhibit cell proliferation and invasion [ 43 ]. Collectively, the choline-induced upregulation of all these placental imprinted genes would be expected to improve placental vascularization and perfusion, likely contributing to the choline-induced beneficial effects on placental transport efficiency and fetal development reported previously [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Neuropilin and tolloid-like 2 ( NETO2 ) has been found in many cancer types including proliferating hemangiomas and colorectal carcinoma [24] , [25] , [26] and thus could be considered as a potential biomarker in tumor progression. Recent study have suggested that adenosine monophosphate deaminase 3 ( AMPD3 ) deletion suppresses the proliferation, migration, and invasion of gastrointestinal stromal tumor [27] . AMPD3 expression is positively correlated with ERG overexpression and PTEN inactivation in prostate cancer [28] , [29] .…”
Section: Discussionmentioning
confidence: 99%